Studi Tentang Persepsi Stakeholders Terhadap Prodi Magister Pendidikan Agama Islam - Maslamah Maslamah (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2019)
This research was motivated by the  competitions phenomenon between  universities  to get the public/stakeholders trust. That’s the public trust have more influence on development of educational institution. Based on those phenomena, Researcher chose the Magister Program of  PAI (Islamic Education) IAIN (State Islamic Institution) Surakarta as field of research. The Magister Program of PAI (MPAI) as new program must built good image for stakeholders.This research was conducted to reveal the perception of Stakeholders on the Magister Program of PAI IAIN Surakarta. This research used qualitative design to analyze  data. The data was obtained through  interview and Focus Group Discussion (FGD), and used the triangulation technic to obtain the data’s validity .The results of this research are the stakeholders internal judged that, 1. MPAI can accommodates the hopes of the graduates of S1,  and teachers in the surrounding area can continue their studies to Magister program; 2. the vision, mission and MPAI curriculum will be able to respon community demans in the future; 3. MPAI still does not have adequate  facilities yet; 4  some stakeholders see that most of the MPAI lectures had the feasibility standard to teach at MPAI; but others don’t agree with the judge.   Key word: Perseption, Stakeholders.